The Relationship Between Gender and Women’s Tobacco Use: An Ecological Analysis with Country-level Data - Hanife Ece Erik; Tülin Çoban; Lütfiye Hilal Özcebe (Thoracic Research and Practice)
OBJECTIVE: Health and well-being are profoundly influenced by gender and its dimensions. This study explores the intricate relationship between gender roles and tobacco use. MATERIAL AND METHODS: The study investigates correlations between the Gender Development Index (GDI), the Global Gender Gap Index (GGGI), and its sub-indicators—critical markers of gender equality—and tobacco prevalence and tobacco-related mortality. Statistical analyses, conducted using the Statistical Package for Social Science and Microsoft Excel, involve Spearman correlation analysis for continuous numerical data and the Kruskal-Wallis H test for differences between means. RESULTS: As per the GDI, a decrease in gender inequality correlates with an increase in tobacco prevalence among women. The highest prevalence of tobacco use in women is found in countries within GDI group 1, with the lowest observed in group 5, characterized by pronounced gender inequality. A moderate positive correlation is identified between the prevalence of tobacco use in women and the GDI, GGGI, and the education sub-component of GGGI. Similarly, a moderate positive relationship is observed between tobacco-related mortality in women and the education subcomponent of GGGI. Education exhibits the highest correlation with both tobacco prevalence and tobacco-related mortality in women. CONCLUSION: The increased prevalence of tobacco use among women in countries with high education and socioeconomic status suggests the early stages of the tobacco epidemic. Smoking cessation remains a persistent challenge, especially for women. The study emphasizes the imperative for tailored gender-specific policies, highlighting the integration of gender considerations into health promotion and public health initiatives.